PENENTUAN KADAR VITAMIN C PADA JERUK MANIS (Citrussinensis) MENGGUNAKAN METODE TITRASI TITRASI NA-2,6 DICHLOROPHENOL INDOPHENOL DAN SPEKTROFOTOMETRI - Siti Nurbaya; Muhammad Taufik; Artha Yuliana Sianipar; Zulfan Zulfan (Jurnal Farmanesia, 2018)
Vitamin C is one of the vitamins that is needed by humans and also one of the water-soluble vitamins, Vitamin C plays a role in the formation of intercellular collagen. For the solubility of vitamins B1, B2, B3, B5, B6, B7, B9, B12, and C are included in the types of water-soluble vitamins, and for the solubility vitamins A, D, E, and K are included in the types of soluble vitamins in fat. Vitamin C functions as an antioxidant and counteracts free radicals that can damage cells. Sources of vitamins are fresh fruits and vegetables. Sweet orange fruit contains vitamin C which is quite high. This study aims to determine and compare the results of vitamin C levels in sweet oranges using the Na 2,6 Dichlorophenol Indophenol titration method and spectrophotometry. The content of vitamin C using Na 2.6 Dichlorophenol Indophenol titration is 0.042%, while the content of vitamin C in sweet oranges using the UV-Vis spectrophotometry method produces levels of 0.351%. These results, shows that the levels of vitamin C obtained by using the UV-Vis spectrophotometry method are higher than those obtained by the iodometric method.